Production of Biomass and Bioactive Compounds Using Bioreactor Technology 2014
DOI: 10.1007/978-94-017-9223-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid Production via Plant Cell Cultures: Biosynthesis, Accumulation and Scaling-Up to Bioreactors

Abstract: Plant cell culture is traditionally viewed as a unique artifi cially created biological system representing a heterogenous population of dedifferentiated cells. This system undergoes a continuous process of autoselection based on the intensity and stability of cell proliferation. We discuss here the details of formation and regulation of isoprenoid biosynthesis in plant cell in vitro based on literature survey and our research. Obviously, secondary metabolism differs in cell culture compared to the plant per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 192 publications
(107 reference statements)
1
28
0
1
Order By: Relevance
“…It has been reported that cell cultures of Dioscorea spp. accumulate predominantly SG of the furostanol type [47]. The content and ratio of individual glycosides in cell culture vary significantly depending on both physical (gas exchange, temperature, bioreactor type) and chemical (medium composition, growth regulators) factors [24,43].…”
Section: Bioreactor Culture Of Dioscorea Deltoidea Suspension Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cell cultures of Dioscorea spp. accumulate predominantly SG of the furostanol type [47]. The content and ratio of individual glycosides in cell culture vary significantly depending on both physical (gas exchange, temperature, bioreactor type) and chemical (medium composition, growth regulators) factors [24,43].…”
Section: Bioreactor Culture Of Dioscorea Deltoidea Suspension Cellsmentioning
confidence: 99%
“…In the present study, the weight content of macro-and micro-elements in D. deltoidea cell biomass was determined using the ICP-MS method. This method has already been tested and used for analyzing macro-and micro-elements content in intact plants and cell cultures [47][48][49][50]. Cultured cells of D. deltoidea contained inorganic marco-and micro-elements that are essential for the human diet [50].…”
Section: Inorganic Elements In Cell Culture Of Dioscorea Deldoideamentioning
confidence: 99%
“…extracts may also contain polyphenols, flavonoids, glycosides, saponins, cyanogenic glycosides, sterols and alkaloids [1,4,6,7]. In Southeast Asia, plants of Polyscias genus are broadly used in traditional medicine; for example, it is recorded in the official Vietnamese Pharmacopoeia as an anti-fatigue and cardiac drug [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fourn.) L. H. Bailey (Araliaceae), an evergreen shrub known as fern leaf Panax, is used in traditional Southeast Asia medicine due to its adaptogenic properties [ 17 ], and for its anti-fatigue, immunomodulating and anti-dizziness activity [ 18 ]. However, its phytochemical constituents are not fully recognized.…”
Section: Introductionmentioning
confidence: 99%